Photothermal Effect: The Amygdaloidal Nano-Structure Based on Bi2S3 for the Enhanced Degradation of Rhodamine B Under Irradiation by NIR - Yin, Xiuzhao; Zhang, Yunyu; Ai, Fujin (Frontiers in Chemistry, 2021)
In recent years the photothermal effect, an auxiliary strategy for increasing the degradation rate of pollutants under irradiation by near-infrared (NIR), has become a research focus. In this study a novel amygdaloidal nanophotocatalyst, Bi2S3, was synthesized by a traditional approach using a hydrothermal process, in which Bi2S3 nanostructures were spread out like a peacock’s tail. The produced Bi2S3 photocatalyst exhibited excellent performance in the rapid degradation of Rhodamine B (RB). This proved that the photothermal effect is mainly responsible for the rapid degradation of RB under NIR laser irradiation. Moreover, it was found that the photothermal effect could not degrade the products with NIR radiation in darkness. However, with the support of visible radiation, the photothermal effect of the Bi2S3 photocatalyst enhanced degradation of RB (degradation rate 90% under 1 h). This novel structure exhibited a potential ability for degrading pollution in industry or agriculture.